Use of Mechanicaly Prepared Iron Nano Particles for Nitrate Removal from Water - Ahmadi, M.; Mashhoon, F.; Kaveh, R.; Tarkian, F. (Asian Journal of Chemistry, 2010)
Zero-valent iron powder has been found to be potentially useful for the removal of nitrate in the water environment. This research is aimed at subjecting the reduction of nitrate by iron nanoparticles produced via physical method. Iron nanoparticles with an average diameter of 25 nm which are characterized by the large specific surface area (40-60 m2 g-1) reduced about 95 % of nitrate within a period of 3 h in the controlled pH = 2-4. Compared with iron nanoparticles produced via chemical method, requirement to acid addition is the most drawback of this iron nanoparticles.